BRUNELLI, A.F.; MUSSALIM, F.; FONSECA-SILVA, M.C. (org.) Língua, texto, sujeito e (inter) discurso. São Carlos: Pedro & João Editores, 2013, 226 p. - Machado, Ida Lucia (Bakhtiniana. Revista de Estudos do Discurso, 2014)
Resenha